Convention Center Arena (Plastichrome of Texas, Inc.)
Part of the three-building Convention Center, the Arena may be used for entertainment spectaculars, sports events or convention sessions. The seating capacity is 10,500, the diameter is 340 feet, and the dome height is 112 feet.